PENGARUH KEMAMPUAN SUMBER DAYA MANUSIA, PRASARANA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - WILDAN AL – AZIZ; SUKRISPIYANTO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2021)
The purpose of this study was to determine and analyze whether the ability of human resources, infrastructure and work environment partially and simultaneously affects the performance of employees of PT. Duta Kharisma Sentosa. The method used in this research is descriptive quantitative, and the nature of this research is explanotary research. The population in this study amounted to 65 respondents. The sampling technique is saturated sample with a sample size of 65 respondents. From the research results, it can be concluded that the coefficient value of the human resource variable is positive and significant (the X1 coefficient is 0.441). shows the value of the coefficient of the infrastructure variable that is positive and significant (the X2 coefficient is 0.377).